The influence of local culture-based simulation learning methods on the interest and learning outcomes of social studies - Gita Ananda; Nursalam Nursalam; Muhammad Nawir (Edumaspul: Jurnal Pendidikan, 2024)
The results of this research show the influence of the interests and learning outcomes of students who were given treatment in the form of the Simulation Based on local culture method compared to students who were not given treatment. Based on the results of the independent sample t-test on hypothesis I, a sig value was obtained. equal to 0.000 < 0.05 then HO is rejected and H1 is accepted, in hypothesis II the sig value is obtained. equal to 0.000 < 0.05, then HO is rejected and H1 is accepted, and the results of the Monova test, obtain a Sig value. 0.000 < 0.05, then HO is rejected and H1 is accepted, meaning that there is an influence of local culture-based simulation learning methods on the interest and learning outcomes of social studies for fifth grade students at SD Negeri Kaluku Bodoa, Tallo District, Makassar City.